ECONOMIC ANALYSIS AND MARKETING STRATEGY IN AGRICULTURAL SUPPLY CHAIN: A CASE STUDY ON W2K ORGANIC FERTILIZER - B Satheesh (African Journal of Environmental Economics and Management, 2023)
The purpose of this study is to determine and analyze the effect of food inflation variables, distribution of staples and distribution of organic fertilizers on increasing food availability through market access as a moderating variable. The existence of food inflation affects the decrease in the availability of food in the market, where this is caused by the limited distribution of organic fertilizers which makes it difficult for farmers to produce food in large quantities, thus disrupting the distribution of food products, because the limited availability of food will increase prices and reduce market access to the public to buy food for their needs. From the results of existing research, it is concluded that partially the variables of food inflation, staple food distribution and organic fertilizer distribution affect the increase in food availability and also affect market access. Simultaneously, the variables of food inflation, staple food distribution and organic fertilizer distribution affect the variable of increasing food availability through market access as a moderating variable. The existence of food inflation affects the decrease in the availability of food in the market, which is caused by the limited distribution of organic fertilizer which makes it difficult for farmers to produce food in large quantities, thus disrupting the distribution of food products, because the limited availability of food will increase prices and reduce market access to the public to buy food for their needs.